Student Engagement and Feedback on Online Learning and Facilitation: A Case Study of the National Open University of Nigeria - Adewale Adesina; Dorothy Ofoha; Olufemi A. Peters; Isaac S. Butswat (West African Journal of Open and Flexible Learning)
With the rapid adoption of online learning platforms occasioned by the rise in digital technologies, the National Open University of Nigeria has continued to leverage technology to optimise operations by offering synchronous online facilitation/tutoring to students as part of its regular academic support initiatives. Online facilitation happens every semester of the academic session. However, since the commencement of online facilitation in 2020, there has been no research report assessing student engagement. Thus, this study was designed to survey students’ online learning experience and gather feedback on various aspects of synchronous online facilitation including participation, satisfaction, barriers, and challenges faced during the virtual learning journey. 2,350 students took part in this study. The survey questionnaire was administered online, featuring a mix of closed-ended and open-ended questions. A majority of students (61.9%) reported participating in the first semester of the 2023 facilitation sessions and expressed satisfaction with their online learning experience, but that more awareness and effective communication strategies are needed to enhance the process. The non-participation rate of 38.1% was attributed to various reasons, with the most common being workloads and personal commitments, unsuitable timetables, financial constraints, limited internet connectivity, and a lack of responsiveness from facilitators in some courses. It is important for NOUN to address these issues by providing more flexible timetables, exploring options for reducing facilitation costs, and ensuring students have access to stable internet connections to improve their engagement in online facilitations. Addressing these challenges can lead to more successful and fulfilling online learning experiences for students.